Host-aware synthetic biology. Issue 14 (April 2019) - Boo, Alice; Ellis, Tom; Stan, Guy-Bart
Abstract: Unnatural gene expression imposes a load on engineered microorganisms which decreases their growth and subsequent production yields, a phenomenon known as burden. In the last decade, the field of synthetic biology has made progress on the development of biomolecular feedback control systems and other approaches that can improve the growth of engineered cells, as well as the genetic stability, portability and robust performance of cell-hosted synthetic constructs. In this review, we highlight recent work focused on the development of host-aware synthetic biology. Graphical abstract: Image 1